Audit Kinerja Manajemen Sumber Daya Manusia Sebagai Strategi Peningkatan Kinerja Karyawan Generasi Z Pada Lingkungan Kerja Era Vuca - Julianto Hutasuhut; Adrial Falahi; Abdurrahman Arrasidi; Aziz Syahputra; Febri Lestari; Muhammad Dzaky; Andhika Dharma Putra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2026)
The evolving work environment of the VUCA era demands that organizations manage human resources in an adaptive, strategic, and sustainable manner, particularly in addressing the distinctive characteristics of Generation Z employees, who prioritize flexibility, work-life balance, and continuous career development. This study examines the role of Human Resource Management Performance Audits as a strategic instrument for enhancing the effectiveness of Generation Z workforce management within the VUCA context. Employing a descriptive qualitative approach through systematic literature review and conceptual analysis, this study encompasses key HR dimensions including planning, recruitment, selection, training and development, performance evaluation, compensation, industrial relations, occupational safety, and organizational culture. The findings reveal that HR Performance Audits function beyond conventional administrative oversight, serving as a comprehensive strategy for strengthening employee engagement, work productivity, training effectiveness, digital competency development, and long-term organizational performance sustainability. Furthermore, HR audits enable organizations to systematically identify systemic weaknesses, optimize HR management efficiency, and reinforce organizational readiness to navigate continuous environmental changes. These audits additionally fortify organizational culture, enhance employee adaptability, and facilitate more informed managerial decision-making amid persistent uncertainty and complexity. Consequently, HR Performance Audits represent a vital mechanism supporting HR transformation, organizational competitiveness, and the achievement of sustainable performance excellence.